Artificial intelligence approaches to fault diagnosis for dynamic systems - Patton, Ron J.; Lopez-Toribio, Carlos J.; Uppal, Faisel J. (Zielona Góra: Uniwersytet Zielonogórski)
Recent approaches to fault detection and isolation (FDI) for dynamic systems using methods of integrating quantitative and qualitative model information, based upon artificial intelligence (AI) techniques are surveyed. In this study, the use of AI methods is considered an important extension to the quantitative model-based approach for residual generation in FDI.
Keywords: artificial intelligence methods; fault-diagnosis; residual generation; fuzzy modelling; neuro-fuzzy systems